Integrated headache care at the outpatient headache center of the University Hospital of Munich: The Munich model. Issue 2 (17th July 2018) - Rohling, Stefan; Funk, Antonia; Ruscheweyh, Ruth; Schankin, Christoph; Straube, Andreas; Kamm, Katharina
Primary headaches, especially migraine, are common disabling neurological disorders with recurrent headache attacks that affect approximately 12–60% of the population. Depending on headache frequency, migraine is often associated with a high socioeconomic burden and a low quality of life. In order to provide adequate treatment for severely affected headache patients, integrated headache care has been established in Germany. It is based on a multimodal and multidisciplinary approach assessing headache diagnosis and offering therapy that has been shown to be effective. This article provides an overview of the structure of integrated headache care at the outpatient headache center at the Munich University Hospital (Upper Bavarian Headache Center). We present different modules of outpatient, day hospital, and inpatient care and discuss clinical outcome for patients utilizing integrated care at our center.